The Effect of the Addition of Tricalcium Phosphate to 5% Sodium Fluoride Varnishes on the Microhardness of Enamel of Primary Teeth - Saeed Aedha AlAmoudi; Sharat Chandra Pani; Mohammad AlOmari (Hindawi Limited, 2013)
Aim. The aim of this study was to compare the effect of pH cycling on the microhardness of the enamel of primary human teeth treated with a conventional brown Sodium Fluoride (5% NaF) Varnish to those treated with a white Fluoride Varnish (5% NaF) enhanced with functionalized tricalcium phosphate (fTCP). Materials and Methods. Ninety extracted caries-free primary incisors were washed in a detergent and divided into three groups; group A received no treatment, teeth in group B were coated with Sodium Fluoride (5% NaF) Varnish, while teeth in group C were coated with 5% NaF varnish enhanced with functionalized tricalcium phosphate (fTCP). After ten days of pH cycling, the surface microhardness of the teeth was measured using a Knoop indenter. Results. The mean Knoop hardness number (KHN) of 5% NaF with fTCP was greater than that of 5% NaF alone while the control group had the lowest mean KHN. Conclusion. The results of this study suggest that the use of an additive such as fTCP to a fluoride varnish significantly improves the protective ability of the varnish on primary teeth in vitro.